Analysis Of The Effect Of Cyberbullying On Teenagers' Body Image And Self-Esteem: Literature Review - Cheisya Nur Fitria; Rafa Fadhilah; Difva Aulya; Erna Julianti (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
The development of information and communication technology has brought about major changes in the way people interact socially, resulting in cyberbullying. The impact of cyberbul lying is a decline in self-esteem and body image. This study aims to explore the results of studies on the effects of cyberbullying on body image and self-esteem in adolescents based on research articles related to the relationship between cyberbullying and body image and self-esteem in adolescents. This study uses a literature review. Articles were collected from several databases such as Google Scholar, EBSCOhost, and Science Direct. The keywords used were cyberbullying, body image, self-esteem, and adolescents. The research article analysis technique used a table format containing the author, title, year, method (design, sample, and analysis), and results. The results show that cyberbullying has a significant impact on the psychological aspects of victims, characterized by decreased self-esteem, increased anxiety, depression, and social isolation, which leads to a decline in academic achievement. The conclusion shows that adolescents have a high level of awareness of the dangers of cyberbullying and its negative consequences on mental health. There is a need to increase education and implement cyberbullying prevention policies, as well as involve schools and parents in creating a safer digital environment.